Angioimmunoblastic T-cell lymphoma and hypereosinophilic syndrome with FIP1L1/PDGFRA fusion gene effectively treated with imatinib: A case report. Issue 36 (September 2017) - Yamamoto, Masayo; Ikuta, Katsuya; Toki, Yasumichi; Hatayama, Mayumi; Shindo, Motohiro; Torimoto, Yoshihiro; Okumura, Toshikatsu
Abstract: Rationale: Hypereosinophilic syndrome (HES) is a rare disorder characterized by hypereosinophilia and organ damage. Some cases of HES are caused by the FIP1L1/PDGFRA fusion gene and respond to imatinib. FIP1L1/PDGFRA -positive HES occasionally evolves into chronic eosinophilic leukemia or into another form of myeloproliferative neoplasm; however, the development of a malignant lymphoma is very rare. We present a rare case of angioimmunoblastic T-cell lymphoma (AITL) and HES with the FIP1L1/PDGFRA gene rearrangement. Patient concerns: A man in his 30s presented to our hospital with fever, hypereosinophilia, widespread lymphadenopathy, and splenomegaly. Laboratory tests showed hypereosinophilia, increased soluble interleukin-2 receptor, and increased vitamin B12. Positron-emission tomography with 18 F fluorodeoxyglucose (FDG) showed positive FDG uptake in multiple enlarged lymph nodes throughout the body and the red bone marrow. A bone-marrow biopsy showed hypereosinophilia without dysplasia and an increased number of blasts. The FIP1L1/PDGFRA fusion gene was positive upon fluorescence in situ hybridization (FISH) analysis of the peripheral blood. Furthermore, biopsy of a lymph node from the neck revealed restiform hyperplasia of capillary vessels, with small lymphoma cells arranged around the capillaries. Lymphoma cells were positive for CD3, CD4, and CD10, and negative for CD20. Lymphoma cells were also positive for the FIP1L1/PDGFRA fusion gene by FISH analysis. Diagnoses: From these findings, the patient was diagnosed with HES and AITL with FIP1L1/PDGFRA. Interventions: After the diagnosis, corticosteroid was administered but was ineffective. Imatinib was then administered. Outcomes: Imatinib was very effective for treating HES and AITL, and complete remission was achieved in both. Lessons: This report presents the first case in which the FIP1L1/PDGFRA fusion gene was positive both in peripheral blood and lymph nodes, implying the possibility that the tumor cells acquired the FIP1L1/PDGFRA fusion gene in the early stage of hematopoietic progenitor cell developments. Imatinib was very effective in treating both HES and lymphoma, suggesting that the FIP1L1/PDGFRA fusion gene plays a key role in the pathogenesis of both HES and lymphoma.